Association Between Metabolic Syndrome and All-Cause Mortality in Patients with Acute Coronary Syndrome: A Meta-Analysis - Yang, Yong; Shen, Haili; Jin, Zhigeng; Ma, Dongxing; Zhao, Qing; Zhang, Xuyi (Hormone and Metabolic Research, 2021)
The association between metabolic syndrome (MetS) and survival outcome after acute coronary syndrome (ACS) remains controversial. This meta-analysis sought to examine the association of MetS with all-cause mortality among patients with ACS. Two authors independently searched PubMed and Embase databases (from their inception to June 27, 2020) for studies that examined the association of MetS with all-cause mortality among patients with ACS. Outcome measures were in-hospital mortality and all-cause mortality during the follow-up. A total of 10 studies involving 49 896 ACS patients were identified. Meta-analysis indicated that presence of MetS was associated with an increased risk of long-term all-cause mortality [risk ratio (RR) 1.25; 95% CI 1.15–1.36; n=9 studies] and in-hospital mortality (RR 2.35; 95% CI 1.40–3.95; n=2 studies), respectively. Sensitivity and subgroup analysis demonstrated the credibility of the value of MetS in predicting long-term all-cause mortality. MetS is associated with an increased risk of long-term all-cause mortality among patients with ACS. However, additional studies are required to investigate the association of MetS with in-hospital mortality.
Keywords: metabolic syndrome; acute coronary syndrome; in-hospital mortality; all-cause mortality